(3GdLGeY GdUMjMs - (3eSde Hf GdMLGL Hf eSde GdbTjQj GdfjSGHhQqi, CHh GdMSjf, CHh GdMSjf,J (B261 (3g` s
(3ChdgG (B:s
(3cJGH GdeXGdje hbhd Gddg YR hLd(B" (3hdGJMSHf Gddg ZGadkG YeG jYed GdXGde (B" (3Edi bhdg(B:" (3Ef Gddg YRjR Ph GfJbGe(B" s
(3BNQgG (B:s
(3abGdJ afMf fbhd ceG bGd QShd Gddg Ydjg hSde Je GdLRA GdKGfi ef KdGK CLRGA ef UMjM GdHNGQi s
(3GdfSNI HgG MhGTs
(3fSNI ecQQI ef GdeNWhW Qbe (B595(3MOjK heUWdMs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B232s
Keywords: (3GdMOjK h GdeUWdMs